Elaboration of Several Ways of Web Technology Scaling on a Particular Case. - Buriánek, Jan; Bruckner, Tomáš, 1974-; Vencovský, Filip; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
Scaling the power of computation is a phenomenon of the last few decades. While that long, this topic is still current and with new and still evolving technologies, new insights has to be discovered to push the human demand for computing forward.The main aim of this project is to measure and compare scalability of an algo-rithm implemented in diverse web technologies. This aim has been approached by reaching three objectives. The first part defines scalability and identifies measures suita-ble for web technology scaling. Number of factors are determined that has direct impact on the runtime performance and the appropriate variables are chosen that become the object of the measurement. Secondly, proper technologies and algorithm are selected enabling the experiment. The testing algorithm is implemented in those technologies and deployed to a testing environment. Finally, aggregated results are drawn from the meas-urement and the final discussion concludes the arising insights.
Vedoucí práce: Tomáš Bruckner
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: kognitivní informatika [obor dipl. práce]; diplomové práce; master's theses